Zmiany konstytucyjne w Polsce Ludowej: [Constitutional changes in the Polish People's Republic] (Studia Prawnicze / The Legal Studies, 1983)
The author analyzes and evaluates the most important constitutional changes introduced during the 40 years of the existence of the Polish People's Republic. The first period (1944-1948) is characterized by dynamic changes in social and economic life (agricultural reform, nationalization of big industry); at the same time legal institutes from the period of 1918-1939 were widely used. The Legislative Diet appointed by general election in 1947 was to adopt a new Constitution of the Polish People's Republic. The Constitution of the Polish People's Republic adopted in 1952, in spite of certain national individual features, referred to the uniform constitutional model which had been accepted by all countries which initiated socialist changes after the Second World War. The norms comprised in the Constitution of the Polish People's Republic are of a general character, therefore it has been binding for a long time with minor modifications of the content. The amendment of 1957, introduced as a result of the events in October 1956, consisted in adding a new chapter about the Supreme Board of Control as a chief organ independent of the government and subordinate only to the Diet and the Council of State.The next, relatively wide amendment, was made in 1976 and was influenced by technocratic concepts of relieving administrative organs from the supervision and control of representative organs.In the years 1980-1983 certain important amendments to the Constitution were made. Their goal was to guarantee the Diet, the highest organ of state authority, to make use of its constitutional rights in relation to the government. The amendment of 1980 which restored full independence of the Supreme Board of Control in relation to the Diet had the same character. The amendment of 1982 brought into being the Tribunal of State as an organ passing decisions on the responsibility of people holding highest posts for the violation of the Constitution and laws, thus legal grounds for the Constitutional Tribunal have been formed which is to evaluate the conformability of laws and other normative acts to the Constitution.The last amendment of July 1983 defined the position of the Patriotic Movement of National Revival in the Political system and also the cooperation of political parties, organizations and associations and citizens in the field of functioning and strengthening of the state and its around development. It guaranteed the stability of individual farms of peasants. It also provided for the possibility to proclaim the state of emergency by the Council of State if internal security of the State has been endangered or in case of a natural calamity. Martial law may be proclaimed only when the defense or security of the State require it.The amendments to the Constitution were of a fragmentary character. Therefore the Constitution of the Polish People's Republic is not a compact document. That is why practice and science of constitutional law have been charged with a task to work out a draft of a new constitution.